PENGEMBANGAN PEANUT BROWNIES SEBAGAI ALTERNATIF MAKANAN SELINGAN UNTUK PENDERITA DIABETES MELITUS - Sofyan, Haris; Mahmudah, Umi; Hapsari, Agustina Indri; Rosmana, Dadang; Hastuti, Widi (Jurusan Gizi Poltekkes Kemenkes Bandung, 2025)
Diabetes Mellitus (DM) is a metabolic disease whose prevalence continues to increase globally, including in Indonesia. Managing DM is closely related to diet, including the consumption of snacks that have a low glycemic index and are high in fiber. This study aimed to develop a Peanut Brownies product made from peanut flour as a functional snack alternative for people with DM. The method used was an experiment with three formulations based on the ratio of peanut flour to cocoa powder (F1 = 60:40, F2 = 50:50, F3 = 40:60). A sensory test using a hedonic scale was conducted with 16 trained panelists, and proximate and fiber content analyses were done in a laboratory. The results showed that formulation F2 had the highest acceptance level and suitable nutritional content as a diabetic-friendly snack, with 163.4 kcal energy, 6.5 g protein, 4.5 g fat, 20.1 g carbohydrates, and 6.8 g fiber per serving. In conclusion, Peanut Brownies with the F2 formulation can be a nutritious and enjoyable snack alternative for people with DM.